The Principles of Language Politeness in Putri Untuk Pangeran Soap Opera - Marthin Herci Brand; I Wayan Budiarta; I Gusti Ayu Agung Dian Susanthi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2022)
This study aims to describe (1) the fulfillment and violations of language politeness, (2) the function of language politeness, and (3) the implicature of language politeness. The theory used in this study is the politeness theory proposed by Leech (1983). This type of research is descriptive qualitative. The method used in this research is to use documentation method, observation method and note taking technique. This type of research is descriptive qualitative. The source of data in this study is 32 downloaded episodes of sinetron that were rerun on RCTI’s official account on YouTube. Researchers used documentation methods, observation methods, and note taking techniques to collect the data. The data that has been collected is classified first. Then the data is analyzed based on fufillment and violation, function and implicature of language politeness. Research results are presented using informal methods. The results shows that there were 5 maxims in Sinetron Putri Untuk Pangeran, namely 7 maxims of wisdom, 8 maxims of generosity, 7 maxims of respect and 1 maxim of violation of respect, 1 maxim of humility and 1 maxim of compatibility maxim and 2 violations of compatibility maxim. The politeness functions found consist of 4 declarative functions, 10 interrogative functions, 31 imperative functions, 4 apologizing functions and 4 criticizing functions. The implicatures contained in this sinteron are 1 conventional implicature, 6 unconventional implicatures and 8 assumptions from implicatures.